Efektivitas Konsumsi Puding Daun Katuk terhadap Peningkatan Kadar Hemoglobin Remaja Putri: Studi Kuasi Eksperimen - Yulien Adam; Fredrika N. Losu; Dian Pratiwi; Sisca D. Solang (Poltekkes Kemenkes Padang, 2025)
Iron deficiency anemia remains a prevalent health issue among adolescent girls, primarily due to increased iron demands during growth and menstruation. This study aimed to evaluate the effectiveness of katuk leaf pudding (Sauropus androgynus) in improving hemoglobin levels in female adolescents at SMPN 02 Lirung, Talaud Islands Regency. A quasi-experimental design with a Non-Equivalent Control Group was employed, involving 64 participants divided into two groups: an intervention group receiving katuk leaf pudding and a control group receiving pudding without katuk leaves, each consisting of 32 respondents. The intervention was administered daily for seven days, with hemoglobin levels measured before and after treatment using a digital hemoglobinometer. Statistical analysis revealed a significant increase in mean hemoglobin levels in the intervention group, from 10.93 g/dL to 11.94 g/dL, whereas the control group exhibited no meaningful change (from 12.57 g/dL to 12.56 g/dL). A paired sample t-test produced a p-value of 0.001, indicating a statistically significant difference. The study concludes that katuk leaf pudding effectively enhances hemoglobin levels among adolescent girls. It is recommended that natural food-based nutritional interventions like katuk leaf products be adopted more broadly and implemented sustainably to prevent anemia in vulnerable populations.